Active Stiffness and Strength in Individuals With Unilateral Anterior Shoulder Instability: A Bilateral Comparison - Olds, Margie (Auckland University of Technology, 2009)
Objective: The objective of this study was to investigate active shoulder stiffness and strength in recurrent shoulder instability. Additionally, this study sought to investigate the relationship between active stiffness, and quality of life, functional outcome, and perceived instability. The relationship between strength and quality of life, functional outcome and perceived instability was also investigated. Study Design: A cross sectional study of a cohort of subjects with unilateral recurrent anterior shoulder instability was undertaken. Background: Recurrent shoulder instability affects up to 94% of young athletes following a dislocation (Rowe & Skallerides, 1961; Rowe & Zairns, 1956). Active stiffness is possibly an important factor in protecting the joint from episodes of instability (Myers, 2001; Riemann & Lephart, 2002). While studies have examined passive stiffness at the shoulder, there is little that has examined active stiffness. Method: Maximal Voluntary Strength (MVS) of the muscles involved in horizontal flexion and their active stiffness at 30%, 50% and 70% MVS was tested in 16 male subjects, with unilateral traumatic anterior shoulder instability. Additionally, quality of life, function and perceived instability were measured using the Western Ontario Stability Index (WOSI), American Shoulder and Elbow Surgeons Questionnaire (ASES) and the Single Alpha Numeric Evaluation score (SANE) respectively. Results: There was a significant decrease in horizontal flexion strength in the recurrently unstable shoulder. Stiffness was also decreased significantly at 30% and 50% MVS. No statistical difference was demonstrated in stiffness values between limbs at 70% MVS. No significant correlation was shown between active stiffness controlling for strength, and quality of life, function or perceived instability. Additionally, no significant association was shown between strength and quality of life, function or perceived instability. Conclusion: The observed reduction in stiffness in the unstable shoulder warrants the inclusion of exercises in the rehabilitation program to enhance this parameter in an effort to protect the joint from perturbations that might lead to dislocation. Deficits in strength in horizontal flexion indicate that strengthening exercises may also be valuable to enhance performance in activities that incorporate horizontal flexion. The lack of an association between active stiffness and quality of life and overall function may indicate that stiffness investigated in one plane of motion does not adequately reflect tissue stiffness during functional activities. Further examination into stiffness in the unstable shoulder is necessary, utilising methodology that examines stiffness in all three dimensions simultaneously.
Keywords: Shoulder; Instability; Stiffness; Strength